Extension of luminance component based demosaicking algorithm to 4- and 5-band multispectral images - Hounsou, Norbert; Sanda Mahama, Amadou T.; Gouton, Pierre (Array (New York), 2021)
Multispectral imaging systems are currently expanding with a variety of multispectral demosaicking algorithms. But these algorithms have limitations due to the remarkable presence of artifacts in the reconstructed image. In this paper, we propose a powerful multispectral image demosaicking method that focuses on the G band and luminance component. We've first identified a relevant 4-and 5-band multispectral filter array (MSFA) with the dominant G band and then proposed an algorithm that consistently estimates the missing G values and other missing components using a convolution operator and a weighted bilinear interpolation algorithm based on the luminance component. Using the considered MSFA patterns, we've also demonstrated that our algorithm outperforms existing approaches both visually and quantitatively in terms of the PSNR and SSIM.